Mathematical model of the snow mass transportation process in the snowblower rotor - D. S. Aleshkov; P. A. Korchagin; I. A. Teterina (Вестник СибАДИ)
Introduction. The complexity and laboriousness of determining the functional dependencies between the structural elements of a rotary snowplow and the developed snow mass when conducting experimental studies on a physical model of a rotary snowplow necessitates the development of mathematical models that make it possible to describe as accurately as possible the processes of interaction between the elements of a rotary snowplow and snow mass. The method of research. A mathematical model of the process of transporting snow mass in a rotor, in which snow is represented as a loose medium, including a set of individual particles, was developed using the method of discrete elements. When constructing a mathematical model, the problems of identifying mass and surface forces acting in the ‘rotor - snow mass’ system were solved. The principle of the location of a group of particles in the interblade space of the snowplow rotor and the choice of the method for analyzing the mathematical model are substantiated.Results. The implementation of this mathematical model on a computer made it possible to obtain the numerical values of the forces of the normal reaction of the rotor casing at each moment of time, which allows developing new and improving existing design schemes, reasonably choosing the design and technological parameters of the rotor of a snow blower.Discussion and conclusion. The proposed mathematical model and the equations of motion, compiled on its basis, make it possible to unambiguously determine the values of all forces acting on the snow mass during its transportation in the rotor of a rotary snowplow. The model under consideration makes it possible to simulate a snow mass in the interblade space of a more complex configuration and a set of particles that have an irregular distribution in size and relative position.